Diagnosing Art Appreciation of Children between the Ages of Four and Nine Years - Mikhailovna Torshilova, Elena; Vyacheslavovna Boyakova, Ekaterina (International Journal of Engineering and Technology, 2018)
This research aims to determine the dynamic development of art appreciation in modern children between the ages of four and nine years. The definition of a child’s art appreciation levels is based on the priority of the aesthetic function of art and children’s ability to harmoniously develop their intelligence and feelings. The article considers different approaches to the diagnosis of artistic preferences within the framework of experimental aesthetics and the modern development of its methods. The authors have prepared a set of special tests to evaluate the development of a child’s art appreciation. They have also described stimulus materials and presented the results of the research held at kindergartens and primary schools. The authors of the article have worked out ethical rules for the test designer diagnosing art appreciation and have concluded that children under five years of age have an aesthetic sensibility that allows them to choose artistic works of "complex" and inexplicit beauty at an emotional, non-rational level. By the age of eight and nine years, the level of a child’s art appreciation declines due to the assimilation of cultural norms of mass art.